Facile manufacture of oxide-free Cu particles coated with oleic acid by electrical discharge machining - Khilji, Irshad Ahamad; Siti Nadiah, Mohd Saffe; Pathak, Sunil; Chilakamarry, Chaitanya Reddy; Amiril Sahab, Abdul Sani; Reddy, Venugopal Jayarama (MDPI, 2022)
Particle synthesis has seen significant advances in current trends. However, the synthesis of metal particles without oxidation is a challenge for researchers. The current study presents a straightforward, convenient, and convincing approach for manufacturing copper (Cu) particles free of surface oxide. The die-sink Electrical Discharge Machine (EDM) of copper alloys with oleic acid resulted in the formation of Cu particles with diameters between 10 to 20 µm. X-ray diffraction (XRD) was used for particle examination after cleaning and sonication with distilled water. Cu particles with oleic acid coating retained a Cu phase without oxidation after synthesis. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were used to determine the size and morphology of generated particles. Fourier transforms infrared (FT-IR) analysis revealed the oleic acid-coated Cu surface bonded with an oxygen atom. Also, the agglomeration and change of size involving Cu particles with increasing voltages in the pulse supply in EDM were reported.